2023
DOI: 10.1088/1361-6528/acbbd2
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced ammonia sensing response based on Pt-decorated Ti3C2T x /TiO2 composite at room temperature

Abstract: Herein, we report a Pt-decorated Ti3C2Tx/TiO2 gas sensor for the enhanced NH3 sensing response at room temperature. Firstly, the TiO2 nanosheets (NSs) are in-situ grown onto the two-dimensional (2D) Ti3C2Tx by hydrothermal treatment. Similar to Ti3C2Tx sensor, the Ti3C2Tx/TiO2 sensor has a positive resistance variation upon exposure to NH3, but with slight enhancement in response. However, after the loading of Pt nanoparticles (NPs), the Pt-Ti3C2Tx/TiO2 sensor shows a negative response with significantly impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 56 publications
(72 reference statements)
0
11
0
Order By: Relevance
“…When RH increased from 20 to 92%, the response to 100 ppm TEA remained significant but decreased from 65.0 to 47.0. This is possibly due to the fact that polar water molecules occupied active sites on the surface of αβγ-BMO MOF nanorods, inhibiting the adsorption of chemical species participating in the detection of TEA. , Overall, the gas response to RH changed by ca. 28%.…”
Section: Resultsmentioning
confidence: 99%
“…When RH increased from 20 to 92%, the response to 100 ppm TEA remained significant but decreased from 65.0 to 47.0. This is possibly due to the fact that polar water molecules occupied active sites on the surface of αβγ-BMO MOF nanorods, inhibiting the adsorption of chemical species participating in the detection of TEA. , Overall, the gas response to RH changed by ca. 28%.…”
Section: Resultsmentioning
confidence: 99%
“…This study showed that Pt NPs shift the response to negative, but enhance the intensity of change in resistance and deliver a sensor response around 10.8 times better as compared with Ti 3 C 2 T x /TiO 2 sensors with lesser response/recovery time. [80][81][82] Guo et al evaluated the sensing performance of the composites to 1 ppm of ammonia gas by varying the WO 3 content in the composites at room temperature. As WO 3 is a conventional n-type semiconductor and pristine WO 3 sensors show an invariable nature of negative response to NH 3 , then, it is a clear conclusion that the positive response of Ti 3 C 2 T x /WO 3 composite to the reducing gas NH 3 is because of the conducting properties of Ti 3 C 2 T x .…”
Section: Dalton Transactions Perspectivementioning
confidence: 99%
“…The synthesis of MXene-TMC/TMD composites can be done in a couple of ways, one of which is ultrasonication of both the powdered samples together in an aqueous solution for around an hour, followed by washing and drying the product. 80 Depending upon the TMDs, the chemical co-precipitation route can also be used in the aqueous solution instead of ultrasonication, in which both the sample powders are added to DI water and stirred to prepare a slurry. This slurry is dried under ambient conditions and the composite is obtained in a powder form.…”
Section: Perspective Dalton Transactionsmentioning
confidence: 99%
“…Surface engineering effectively lowers operating temperatures by increasing the degree of specific surface area defects. However, it was not easy to improve the response or recovery speed of sensing devices. , In the doping area, the strategies adopted are mainly noble metal nanoparticle (Pd, Pt, Au, Ag, and Rh) modification. Because of spillover phenomena and electronic effects, noble metal doping promotes gas-sensing properties.…”
Section: Introductionmentioning
confidence: 99%